Clinical analysis of high-intensity focused ultrasound (HIFU) combined with hysteroscopy-guided suction curettage (HGSC) in patients with cervical pregnancy. (31st December 2022) - Huang, Yufu; Zhu, Xiaogang; Wang, Luying; Ye, Mingzhu; Xue, Min; Deng, Xinliang; Sun, Xin
Abstract: Objective: To evaluate the effectiveness of high-intensity focused ultrasound (HIFU) combined with hysteroscopy-guided suction curettage (HGSC) in treating cervical pregnancy. Materials and methods: This is a retrospective study. Seven patients with cervical pregnancy who visited the Third Xiangya Hospital of Central South University from January 2015 to December 2020 were enrolled in the current study. All seven patients were treated with HIFU under conscious sedation. All of them underwent HGSC at an average of 2 ± 1 days (range: 1–3 days) after HIFU. Before the therapy, the patient's clinical characteristics were collected, including duration of amenorrhea, gravidity and parity, the patient history of cesarean section and miscarriage, and the size of the gestational sac. The levels of β-hCG and hemoglobin in serum were also reviewed. To assess the clinical outcomes of this combined treatment, the suction time of HGSC, bleeding volume, the clearance time of β-hCG, and the time with returning of menstruation were evaluated. Results: All seven patients (average age: 31 ± 6 years) have experienced amenorrhea (duration range, 48 ± 8 days) before the treatment of HIFU. The average number of pregnancies was four, and the number of deliveries was one. Previous medical history showed six patients had cesarean sections, and five patients have been miscarriages. After HIFU treatment, the fetal heartbeats were stopped in all seven patients based on the diagnosis by doppler ultrasound. The bleeding of gestational tissue decreased significantly. All patients had only mild lower abdominal pain, no fever, intestinal damage, or other complications were reported. The average operation time of operative suction curettage was 21 ± 9 min (range: 9–32 min), and the median bleeding volume was 10 ± 8 mL (range: 2–20 mL). Follow-up observations showed that the menstruations were returned in patients at an average of 38 ± 9 days (range: 30–50 days) after the treatment. The β-hCG decreased from 41773 ± 32242 mIU/mL to 13101 ± 8454 mIU/mL in 29 ± 10 days after surgery. Conclusion: Based on these results with small subjects, we concluded that HIFU combined with HGSC might be an effective and safe treatment for patients with cervical pregnancy.